Female Athlete Health, Performance, and Menstrual Cycle Monitoring in Competitive Sports - Dr. Bhaskar Ankem (The Bioscan, 2021)
The health and performance of female athletes are shaped by physiological factors that male athletes do not experience, the most distinctive of which is the menstrual cycle. For many years the cycle was treated as a complication to be avoided in research rather than a variable to be understood, and as a result female athletes have often trained without guidance on how their cycle affects them. This study examined the awareness and practice of menstrual cycle monitoring among female competitive athletes and the perceived impact of the cycle on their training, performance and recovery. A descriptive cross-sectional survey was conducted among one hundred and eighty female competitive athletes aged eighteen years and above in the north coastal districts of Andhra Pradesh. A structured questionnaire gathered information on menstrual characteristics, monitoring habits, awareness of female-athlete health issues and the perceived effect of the cycle across its phases. Percentage analysis, mean, standard deviation, the chi-square test and the Friedman test were used in the analysis. The findings show that menstrual dysfunction was common, that systematic monitoring was practised by only a minority, and that awareness of broader female- athlete health concerns such as low energy availability was limited. Regular monitoring was significantly associated with better awareness and management of menstrual health, and the perceived impact on performance differed significantly across the phases of the cycle, being greatest during menstruation and the premenstrual phase. The study concludes that structured menstrual cycle monitoring and dedicated education are needed to protect the health and support the performance of female athletes.